Serum osteoprotegrin (OPG) in subclinical atherosclerosis in systemic lupus erythematosus. (July 2017) - Kiani, A N; Aukrust, P; Ueland, T; Hollan, I; Barr, E; Magder, L S; Petri, M
Introduction: Osteoprotegerin (OPG) is a member of the tumor necrosis factor (TNF) receptor family. It has recently been demonstrated that OPG is produced by a variety of tissues, including the cardiovascular system (heart, arteries, veins), lung, kidney, immune tissues, and bone. The OPG-RANKL signaling pathway is strongly related to vascular calcification. We determined the association of this biomarker with subclinical atherosclerosis in systemic lupus erythematous (SLE). Methods: We measured OPG and markers of subclinical atherosclerosis (coronary artery calcium (CAC), carotid intima-media thickness (cIMT) carotid plaque) in 166 SLE patients (91% female, 64% Caucasian, 31% African American, 5% others, mean age 45 years). Subgroups of patients with different levels of OPG level were compared with respect to average levels of CAC, cIMT, and with respect to presence of carotid plaque. Age was adjusted for using multiple regression. Results: OPG was highly correlated with age ( p < 0.0001). Individuals with higher levels of OPG tended to have higher measures of CAC, cIMT, and more carotid plaque. However, after adjustment for age, these associations, while still positive, were no longer statistically significant. Conclusion: In our study much of the association observed was due to confounding by age, and after adjusting for age, our findings do not rule out the possibility of a null association.